EVALUASI EFEKTIVITAS PELATIHAN KERJA KARYAWAN MENGGUNAKAN MODEL KIRKPATRICK DI PT GOMEDS NETWORK, GORONTALO - Hamdan Istutiawan Humonggio; Musafir Musafir; Arifin Arifin (Universitas Ichsan Sidenreng Rappang, 2026)
Human resource development is a strategic factor in enhancing organizational competitiveness, particularly in the internet service industry, which faces rapid technological development and increasing service quality demands. This study aims to evaluate the effectiveness of employee training at PT Gomeds Network Gorontalo using the Kirkpatrick Model, consisting of four evaluation levels: reaction, learning, behavior, and results. This study employed a qualitative approach using a case study method. Informants included company management, training administrators, direct supervisors, and employees who had participated in training programs. Data were collected through in-depth interviews, observation, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that participants responded positively to the training because the materials were relevant to job requirements and supported by competent instructors. Training improved technical knowledge, operational skills, and understanding of work procedures. Behavioral changes were reflected in improved compliance with standard operating procedures, problem-solving abilities, teamwork coordination, and application of training outcomes in daily tasks. At the results level, training contributed to improved service quality, operational effectiveness, faster network disruption handling, and achievement of Service Level Agreement (SLA) targets. Supervisor support and organizational culture were key supporting factors, while time constraints and workload were major challenges.